IMPLEMENTASI PERATURAN MENTERI DALAM NEGERI NOMOR 2 TAHUN 2016 TENTANG KARTU IDENTITAS ANAK DI KABUPATEN PASAMAN - Sari, Lara Nadia; As’ari, Hasim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The Child Identity Card is a policy issued by the Government by issuing an identity card that is officially recognized for children under 17 years of age as an effort to improve data collection, protection and public services for children. The implementation of the Child Identity Card policy began in 2019 in Pasaman Regency which was carried out by the Pasaman Regency Population and Civil Registration Service. In its implementation, there are problems, namely there are still people who do not know the Child Identity Card policy and there is still a lack of public awareness to take care of it so that the issuance of Child Identity Cards in Pasaman Regency is still low. For this reason, the authors are interested in conducting research related to the implementation of Minister of Home Affairs Regulation Number 2 of 2016 concerning Child Identity Cards in Pasaman Regency. The purpose of this study is to determine the implementation of the Minister of Home Affairs Regulation Number 2 of 2016 concerning Child Identity Cards in Pasaman Regency and to determine the factors that hinder the implementation of the child's identity card policy. The theory used in this research is the theory of policy implementation by Van Meter and Van Horn. To answer these problems, researchers used a qualitative method with a descriptive approach. In this study the authors used data collection techniques in the form of observation, interviews and documentation then analyzed based on the research problem. The results of this study indicate that the implementation of the Minister of Home Affairs Regulation Number 2 of 2016 concerning Child Identity Cards in Pasaman District has not been well realized. The factors that hinder the implementation of Minister of Home Affairs Regulation Number 2 of 2016 concerning Child Identity Cards in Pasaman Regency are related to material resources, socialization and negative public opinionKeywords: Policy Implementation, Child Identity Card